2006
DOI: 10.1051/0004-6361:20066001
|View full text |Cite
|
Sign up to set email alerts
|

A Sino-German $\mathsf{\lambda}$6 cm polarization survey of the Galactic plane

Abstract: Aims. Polarization measurements of the Galactic plane at λ6 cm probe the interstellar medium (ISM) to larger distances compared to measurements at longer wavelengths, enabling us to investigate properties of the Galactic magnetic fields and electron density. Methods. We are conducting a new λ6 cm continuum and polarization survey of the Galactic plane covering 10• ≤ l ≤ 230• and |b| ≤ 5• . Missing large-scale structures in the U and Q maps are restored based on extrapolated polarization K-band maps from the WM… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
139
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(146 citation statements)
references
References 56 publications
7
139
0
Order By: Relevance
“…The actual distance from γ Cas to IC 63 is d⋆ = d ⋆,sky / cos(58 • ) = 2.45pc. In addition, both the position angles of the optical polarization in the nebula and synchrotron measurements in the area encompassing IC 63 (Sun et al 2007) show a projected magnetic field closely parallel to the Galactic plane. While direct determinations of the three dimensional structure of the magnetic field in the region are not available, we can estimate the over-all field orientation by assuming that it follows the spiral arms.…”
Section: Physical Model Of Ic 63 and Model Set Upmentioning
confidence: 93%
“…The actual distance from γ Cas to IC 63 is d⋆ = d ⋆,sky / cos(58 • ) = 2.45pc. In addition, both the position angles of the optical polarization in the nebula and synchrotron measurements in the area encompassing IC 63 (Sun et al 2007) show a projected magnetic field closely parallel to the Galactic plane. While direct determinations of the three dimensional structure of the magnetic field in the region are not available, we can estimate the over-all field orientation by assuming that it follows the spiral arms.…”
Section: Physical Model Of Ic 63 and Model Set Upmentioning
confidence: 93%
“…Stokes parameters I, U, and Q were stored simultaneously for each map. The system set-up and the data reduction were described in detail by Sun et al (2006Sun et al ( , 2007 and Gao et al (2010).…”
Section: The λ6 CM Survey and The Large Snrsmentioning
confidence: 99%
“…Instrumental effects in Stokes U and Q maps were corrected for the leakage of total intensity I into the polarization channels as described by Sun et al (2007).…”
Section: The λ6 CM Survey and The Large Snrsmentioning
confidence: 99%
“…There are also some individual discoveries, although not many. The SinoGerman λ6 cm polarization survey of the Galactic plane 1 (Sun et al 2007(Sun et al , 2011a; Gao et al 2010;Xiao et al 2011) conducted by the Urumqi 25-m radio telescope provides a good hunting ground for discovering new Galactic SNRs. Gao et al (2011) identified two new faint SNRs G25.1−2.3 and G178.2−4.2.…”
Section: Introductionmentioning
confidence: 99%